Proceso de atención de enfermería en paciente hemodializado de 54 años con sepsi del cateter venoso central. - Ramírez Gavilán, Jairo David (2020)
Central venous catheter sepsis in hemodialysis patients due to the presence of chronic renal failure is a very common problem in health data, due to the fact that it has a direct access point for the entry of microorganisms directly into the bloodstream causing an index high morbidity or consequences that directly affect people's health status. The proper application of the nursing care process such as assessment, planning, execution and evaluation, allows obtaining a large amount of updated knowledge of great importance for the training of health personnel, this clinical case study mentions at the same time how fundamental it is the application of adequate, precise and systematic nursing care for the comprehensive recovery, prevention and rehabilitation of patients. This clinical study will allow students, health personnel, and teachers to have a source of acquisition of care plans that have been proven and have given a good result in the direct evolution with the patient, also fundamentally the importance of effective communication nurses - patient to obtain truthful information and at the same time create a connection of trust giving the patient the opportunity to express their emotions and fears.